Workshop Jurnalistik Online bagi Pemuda Desa Pengembur Kecamatan Pujut Kabupaten Lombok Tengah - Muhammad Jamiluddin Nur; Aurelius Rofinus Lolong Teluma; Diyah Indiyati (Jurnal Gema Ngabdi, 2023)
The purpose of this community empowrement is to provide online journalism skills to youth in the Pengembur Village, Central Lombok. This activity was attended by the Head of Pengembur Village, Mosque Youth, Pengembur Youth Organization, village operators and other village apparatus. There is a lot of potential in the Pengembur Village, but the publication of information related to the Pembur Village is still very minimal. This is due to the lack of ability of youth to produce journalistic content, especially through online media. After doing this service, the youth have skills including; determine priority issues, divide tasks when carrying out coverage, write and edit coverage results, publish and distribute journalistic contexts that youth have worked on.